ANALISIS PENGARUH PERPUTARAN KAS, PIUTANG, DAN PERSEDIAN TERHADAP PROFITABILITAS PERUSAHAN PT. BUMI IRIAN INDAH (BII) - Wangsi, Mitta Muthia; Haurissa, Yane Listy (Mount Hope Economic Global Journal, 2023)
This research aims to determine the analysis of the influence of working capital/current assets on profitability. This working capital / current assets turnover includes cash turnover, inventory turnover, and accounts receivable inventory. Bumi Irian Indah Company's financial report is used as secondary data in this research with a time period of 2018-2020. Multiple linear regression, T test and F test are used as analysis methods. The conclusion of this research analysis is that working capital/current asset turnover has a simultaneous effect on profitability, while only partial inventory and receivables have an effect on profitability.